Patient-Level Factors Associated with Antihypertensive Prescribing Patterns in a Free Clinic Setting - Leah Barnes; Avaneesh Kunta; Taylor Ham; Oliver Nguyen; Anshul Daga; Kartik Motwani; David Feller (Journal of Student-Run Clinics, 2025)
Background: Hypertension is the world’s leading cause of cardiovascular disease and premature death. In the United States, non-White adults have higher rates of hypertension, yet lower rates of treatment. Furthermore, underinsured and uninsured populations experience unique barriers, receive fewer and lower quality healthcare services, and are the focus of less research; however, student-run free clinics (SRFCs) help address this gap and treat conditions like hypertension. This study assessed patient-level factors that may influence prescribing patterns for hypertension at SRFCs.Methods: A chart review was conducted on patients diagnosed with hypertension (N=799) seen from January 2013-February 2020 inclusive at one SRFC network. The outcome variable was receipt of antihypertensive medication. A logistic regression analysis assessed the association between antihypertensive prescribing and patient-level variables (age, comorbidities, race, sex, education, language, housing, insurance status, transportation, employment status).Results: After controlling for other factors, those with two or more comorbidities were more likely to be prescribed an antihypertensive than those with no comorbidities (odds ratio [OR] 1.31, 95% Confidence interval [CI] 1.04-1.65, p=0.021). When compared to non-Hispanic White patients, Hispanic patients were around 40% less likely to be prescribed an antihypertensive (OR 0.58, 95% CI 0.36-0.92, p=0.03). Insured patients were 60% less likely to be prescribed an antihypertensive than uninsured patients (OR 0.40, 95% CI 0.22-0.75, p=0.004).Conclusions: This study found that, at an SRFC network, differences in antihypertensive prescribing exist by comorbidities, race, and insurance status, indicating patient-level hypertension treatment disparities in this population. This study suggests the need for research into how patient-level factors influence physicians’ treatment decisions and how educating SRFC patients about medication assistance programs can mitigate insurance-related disparities.